SIGNIFICANT CONTRIBUTION TO THE PAINTING OF COLORS: रंगों का चित्रकला में महत्वपूर्ण योगदान - Shukla, Anshuli (International Journal of Research -GRANTHAALAYAH, 2014)
Since prehistoric times, colors have been the mainstay of painting. The role of colors in painting reveals charm and beauty. Generally, nature is a mine of colors. According to scientists, colors originate from sunlight, which combines colors. The combination of colors is visible in many styles under Indian art such as Ajanta style, Pal style, Apabhramsa style, Rajasthani style, Mughal style, Deccan style, Pahari style etc. Similarly, painting of Kerala also plays a special role in the context of painting colors of South Indian states. In which first of all the pictures painted in the cavity temples come. प्रागैतिहासिक काल से ही चित्रकला में रंगों का मुख्य स्थान रहा है। चित्रकला में रंगों की भूमिका आकर्षण एवं सुन्दरता को प्रकट करती है। सामान्यतः प्रकृति रंगों की खान है। वैज्ञानिकों के अनुसार, रंगों की उत्पत्ति सूर्य के प्रकाश से हुयी है जिसमें रंगों का समावेश मिलता है। रंगों का संयोजन भारतीय कला के अन्तर्गत कई शैलियों जैसे-अजन्ता शैली, पाल शैली, अपभ्रंश शैली, राजस्थानी शैली, मुगल शैली, दक्खन शैली, पहाड़ी शैली आदि में दृष्टव्य है। इसी प्रकार दक्षिण भारतीय राज्यों की चित्रकला रंगों के परिप्रेक्ष्य में केरल की चित्रकला भी विशेष भूमिका रखती है। जिसमें सर्वप्रथम गुहा मन्दिरों में चित्रित भिŸिा-चित्र आते हैं।